Atezolizumab in urothelial bladder carcinoma. (February 2018) - Hamilou, Zineb; Lavaud, Pernelle; Loriot, Yohann
Metastatic bladder cancer is an aggressive malignancy with a poor prognosis when presenting with advanced stage. Cisplatin-based therapy has been the mainstay of first-line treatment but therapy in second-line setting has been an unmet medical need for decades. Moreover, many patients are unable to receive cisplatin-based therapy. Recently, immune-checkpoint inhibitors transformed the management and prognosis of many malignancies and will certainly redefine the standard of care for bladder cancer. Atezolizumab, an anti-PD-L1 antibody, was the first immune-checkpoint inhibitor to be approved by the US FDA in May 2016 for patients with urothelial carcinoma. In this review, we discuss the evidence behind this promising drug.